95 years of climate and cryosphere studies of the Arctic in the Arctic and Antarctic Research Institute - G. V. Alekseev; D. Yu. Bolshiyanov; V. F. Radionov; S. V. Frolov (Лëд и снег)
A brief description of studies of the atmosphere, ocean, sea ice, and glaciers in the Arctic Regions and on the islands fulfilled since 1920 by scientists and specialists of the Arctic and Antarctic Research Institute (AARI) is presented. The paper is dedicated to the 95th anniversary of the Institute.